Enhancing the Multi-dimensional Assessment of Quality of Life: Introducing the WHOQOL-Combi - Skevington, SM; Rowland, C; Panagioti, M; Bower, P; Krägeloh, Chris (Springer Nature, 2020)
Introduction: We revisited the global concept of subjective quality of life (QoL) as assessed by the WHOQOL-BREF to investigate whether it could be elaborated into a conceptually more comprehensive instrument with good psychometric properties. Responding to a growing need for shorter QoL measures with broader social, spiritual and environmental contents, facets from WHOQOL international modules were examined for potential integration into the new WHOQOL-Combi. Method: Adults over 65 years, diagnosed with one or more chronic diseases (n = 2833), completed 41 WHOQOL items during the CLASSIC survey; each item represented a WHOQOL facet. This pool of specific QoL facets contained 24 from the WHOQOL-BREF (excluding general items), and 17 from recent international WHOQOL short-form modules, selected for their generic properties. Rasch modelling reduced the final item pool when assessing the WHOQOL-Combi’s conceptual structure. Comparisons are made with the WHOQOL-BREF. Results: Modelling confirmed the tenability of a 36-item solution scored as a five-domain profile, comprised of 24 WHOQOL-BREF facets and 12 new facets from modules. Social and psychological domains were strengthened by three facets, spiritual QoL by five, and physical QoL by one. The WHOQOL-Combi showed sound model fit, excellent internal consistency (α =.95), and scores discriminated between socio-demographic categories. Concurrent validity with the EQ-5D-5L was confirmed for physical and psychological domains. Performance was similar to the WHOQOL-BREF. Conclusion: The WHOQOL-Combi offers a contemporary, comprehensive, integrated, multi-dimensional subjective QoL instrument with enhanced evaluations of social, spiritual, psychological and physical QoL. Acceptable to older people, future research should evaluate younger age groups and other cultures.